PERLAKUAN AKUNTANSI TERHADAP SOFWARE PADA DINAS PERHUBUNGAN KABUPATEN TANAH DATAR BERDASARKAN SAP NO. 14 TENTANG ASET TIDAK BERWUJUD - Sri Adella Fitri; Lefri Gusdi; Miftahul Fajriani; M.Dian Saputra; Putri Sundari (Universitas Islam Negeri Alauddin Makassar, 2023)
The development of accounting in the Indonesian government can be said to be very slow to anticipate the demands of the times. The output produced by government accounting in Indonesia cannot be said to be accurate and not informative, so it cannot be used in decision making. Government Regulation No. 24 of 2005 describes Government Accounting Standards, hereinafter referred to as SAP, are accounting principles applied in preparing and presenting government financial reports. Based on this government regulation, the central and regional governments must apply full accrual-based accounting and no longer apply cash-based accounting. towards accruals. This research tends to determine the accounting treatment of software at the Office of Communication and Information Technology based on SAP No.14 regarding intangible assets. This research is quantitative research method with a descriptive approach with data collection techniques in the form of interviews, observation, and documentation. The results of the study show that the accounting treatment of software in the Office of Transportation Office which has 1 software, namely Simda BMD and Recognition and Measurement alone, there is no violence and termination of the software in this transportation service, there are also no disclosures related to the software.